Feeding infant formula with low sn-2 palmitate causes changes in newborn’s intestinal environments through an increase in fecal soaped palmitic acid - Atsushi Ito; Hiromichi Shoji; Hiroko Arai; Satsuki Kakiuchi; Keigo Sato; Shinji Jinno; Naoto Takahashi; Kenichi Masumoto; Hitoshi Yoda; Toshiaki Shimizu (PLoS ONE, 2025)
Background/Objectives Soaped palmitic acid (PA) has been reported to be excreted in stool after feeding infant formulas containing low sn-2 palmitate levels, which corresponds to high sn-1 or -3 palmitate levels. While an in vitro study showed that soaped PA inhibits the Bifidobacteria growth, few clinical studies have evaluated effects of soaped PA on intestinal environments of infants. In this study, we aimed to evaluate associations between increased fecal soaped PA levels and inhibition of growth of the intestinal microbiome using clinical data, and to evaluate changes in the intestinal environment with formula-feeding. Methods This study was conducted as a secondary analysis to our observational study of Japanese 1-month-old infants (n = 172). Infant formulas were classified into high sn-2 formula (≥ 50%) and low sn-2 formula (< 50%) according to the sn-2 binding ratio of PA. Multiple regression analyses and path analysis were performed as statistical analyses. Results In the multiple regression analysis, the occupancy of Bifidobacteria was negatively correlated with the fecal soaped PA levels (β = −0.15, 95% confidence interval = −0.28– − 0.02). A path analysis suggested that low sn-2 formula feeding led to increased fecal soaped PA levels, decreased Bifidobacteria occupancy, and finally increased fecal pH. Conclusions Our clinical data showed significant associations between higher fecal soaped PA levels and lower Bifidobacteria occupancy in the newborn gut, which agreed well with the report of the in vitro study. Our study also suggests that feeding infant formula with low sn-2 palmitate causes changes in the intestinal environment through an increase in fecal soaped palmitic acids.